OP17 A molecular measure of inflammation in IBD patients based on transcriptional profiles from 2495 intestinal biopsies. (25th January 2019) - Huang, R; Irizar, H; Kosoy, R; Song, W-m; Dinarzo, A; Hao, K; Rogers, J; Atreja, A; Mahajan, M; Stojmirovic, A; Perrigoue, J; Brodmerkel, C; et al.
Abstract: Background: Endoscopy, histology, and biomarker measures of inflammation have limitations of sensitivity, specificity, reproducibility, and range in evaluating inflammatory bowel disease (IBD). We explored whole transcriptome gene expression to define molecular scores of gut inflammation. These scores are applicable to both Crohn's disease (CD) and ulcerative colitis (UC), enabling more granular, continuous measures across multiple states and location of disease. Methods: We present a molecular characterisation of IBD based on the transcription profiles of 719 endoscopically defined inflamed (Inf) and 1776 non-inflamed (NInf) intestinal biopsies from 498 CD, 419 UC patients in the Mount Sinai Crohn's and Colitis Registry (MSCCR) during endoscopy. Genes differentially expressed between Inf and NInf biopsies were used to generate a biopsy-level molecular inflammation score (MIS) via gene set variation analysis. 1 Results: MIS was strongly associated with histological biopsy scores for CD (GHAS 2 ) and UC (Nancy Index 3 ) and independent of inflammatory status (Inf B = 3.1, NInf B = 2.73; p > 0.05) (Figure 1A), MIS of Inf biopsies was higher than NInf within the same histological score, indicating that MIS describes a broader range of inflammation signal than histologic assessment. MIS was also associated with endoscopically defined severity (SES-CD and Mayo-endo for UC); capturing the gradient from mild, moderate, to severe disease (Figure 1B). Association of MIS with clinical disease severity was significant for Inf biopsies for continuous measures (HBI for CD B = 0.65, p < 0.01; SCCAI for UC B = 1.94, p < 0.01) and could also differentiate between HBI and SCCAI defined active and inactive subsets (UC d = 11.5, p < 0.01; CD d = 5, p < 0.01). This was not the case for NInf biopsies (Figure 1C), indicating that the clinical scores track with inflammation but not with homeostatic features of the gut. Conclusions: We generated a transcriptionally based intestinal inflammation score in IBD patients, which provides an objective quantification of disease state in IBD-relevant tissues. MIS scores are associated with features captured by histological, endoscopic, and clinical evaluations, but do so with a greater dynamic range, and as a common metric for CD and UC. Further work will explore whether MIS may improve patients subsetting, identify sub-clinical disease, predict flares or therapeutic response. Furthermore, MIS can be used to regress the inflammation component, revealing novel non-inflammatory mechanisms. References 1. Hänzelmann S, Castelo R, Guinney J. GSVA: gene set variation analysis for microarray and RNA-seq data. BMC Bioinf . 2013;14:7. 2. D'Haens GR, Geboes K, Peeters M, et al . Early lesions of recurrent Crohn's disease caused by infusion of intestinal contents in excluded ileum. Gastroenterology . 1998;114:262–7. 3. Marchal-Bressenot A, Salleron J, Boulagnon-Rombi C, et al . Development and validation of the Nancy histological index for UC. Gut, 2017;66:43–9.